2006
DOI: 10.1111/j.1600-6143.2006.01307.x
|View full text |Cite
|
Sign up to set email alerts
|

Acute and Chronic Vascular Rejection in Nonhuman Primate Kidney Transplantation

Abstract: A nonhuman primate (NHP) study was designed to evaluate in nonlife-supporting kidney allografts the progression from acute rejection with transplant endarteritis (TXA) to chronic rejection (CR) with sclerosing vasculopathy. Group G1 (n = 6) received high cyclosporine A (CsA) immunosuppression and showed neither TXA nor CR during 90 days posttransplantation. Group G2 (n = 6) received suboptimal CsA immunosuppression and showed severe TXA with graft loss within 46 days (median). Arterial intimal changes included… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
26
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(31 citation statements)
references
References 36 publications
4
26
1
Order By: Relevance
“…This finding suggests that PDGF-D, together with PDGF-A and -B, participates in the pathogenensis of transplant arteriopathy in an organized sequence of activities. This proposed scenario is consistent with the evolution of morphologic changes recently described in a non-human primate model of chronic vascular rejection which also suggest that many if not all of the cases of CAN in our series are indeed the result of chronic rejection [29]. Our findings do not identify what may be the functional role of PDGF-D that appears to be constitutively expressed by vascular medial smooth muscle cells.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…This finding suggests that PDGF-D, together with PDGF-A and -B, participates in the pathogenensis of transplant arteriopathy in an organized sequence of activities. This proposed scenario is consistent with the evolution of morphologic changes recently described in a non-human primate model of chronic vascular rejection which also suggest that many if not all of the cases of CAN in our series are indeed the result of chronic rejection [29]. Our findings do not identify what may be the functional role of PDGF-D that appears to be constitutively expressed by vascular medial smooth muscle cells.…”
Section: Discussionsupporting
confidence: 87%
“…Chronic allograft arteriopathy is one of the main pathological manifestations of CAN, which is characterized by neointima formation by mesenchymal cells with accumulation of sclerotic matrix in arteries [1,3]. This arteriopathy is often a consequence of rejection, as recently detailed in studies of a non human primate model of transplant rejection [29], and it is likely most of the cases of CAN included in the present study are a consequence of chronic vascular rejection. Current leading opinions about the origin of the mesenchymal neointimal cells in this arteriopathy is that they are derived either from smooth muscle cells that have migrated from the vessel media as a result of stimulation by growth factors and cytokines released during vascular injuries, or that they are derived from myofibroblasts migrating from the vascular adventitia.…”
Section: Discussionmentioning
confidence: 70%
See 1 more Smart Citation
“…In contrast, germinal centers in the 100 mg/kg group were unobservable in all analyzed organs in the present study, whereas germinal centers had been clearly observed in our previous study in naive cynomolgus monkeys [14]. Wieczorek et al reported that groups which received high CsA immunosuppression showed less acute rejection with transplant endarteritis to chronic rejection with sclerosing vasculopathy than groups which received suboptimal CsA immunosuppression in nonhuman primate kidney transplantation [18]. Therefore, at the dose level of CsA in the present study, the histological changes of the lymphoid tissue were considered to be changes resulting from beneficial effects of CsA.…”
contrasting
confidence: 73%
“…This species is often used for biomedical research [7,21] involving infectious diseases, such as AIDS [43], influenza [17], tuberculosis [6,15], measles virus [30], western equine encephalitis virus [27], and severe acute respiratory syndrome (SARS) [1�]� neuro- [1�]� neuro-� neurological diseases, such as Alzheimer's disease [40] and Parkinson's disease [8]� reproduction [33]� regenerative medicine [31]� transplantation [4,18,25,41,42]� and immunotherapy [22,32]. In order to effectively use cynomolgus macaques for medical research, it is necessary to better understand the genetic diversity among and within the different populations.…”
Section: Introductionmentioning
confidence: 99%